PENINGKATAN SELF EFFICACY MASYARAKAT MELALUI PELATIHAN KEBENCANAAN FADIP (FIRST AID AND DISASTER PLAN TRAINING) - Suindrayasa, I Made; Manangkot, Meril Valentine; Saputra, I Kadek; Wibawa, Ari (Coping: Community of Publishing in Nursing, 2024)
In disaster conditions, preparation for response and mitigation must be prepared with good self-efficacy. Self-efficacy in disasters is an individual's self-confidence in the strength they have to be able to overcome disaster conditions. FADIP Disaster Training (First Aid and Disaster Plan Training) is training that contains topics on disaster preparation, management and mitigation. Tista Village is a tourist village located in the developing Tabanan Regency, Bali Province. The tourism industry must be supported by various aspects, especially health. The problem formulation in this research is whether there is an increase in community self-efficacy through FADIP in Tista Tourism Village, Tabanan Regency. The aim of this research is to increase community self-efficacy through FADIP in the Tista Tourism Village, Tabanan Regency. The method in this research is a descriptive analytical method with a quasi experiment method with pre-post test. The sample for this research is respondents who are/live in the Tabanan Regency Tourism Village area. The number of respondents was 30 people. Data were analyzed using the Wilcoxon test. The research results showed that the p-value was < 0,05 which means there was an increase in community self-efficacy through FADIP in the Tista Tourism Village, Tabanan Regency.